PENGEMBANGAN DAN VALIDASI METODE KCKT PADA PENENTUAN KADAR MORAKHALKON A SEBAGAI SENYAWA MARKER DALAM EKSTRAK ETANOL 80% KULIT BATANG Artocarpus champeden SPRENG - EVI KURNIAWATI, 051414153005 (2017)
Artocarpus champeden SPRENG., commonly known as “cempedak” has been traditionally used for malarial remedies. In order to develop A. champeden as antimalarial phytopharmaceutical product, marker approach was choosen for quality control purpose of the extract as raw material. Morachalchone A is the active marker of ethanol extract Artocarpus champeden. To ensure the quality, efficacy and safety of the phytopharmaceutical products, a simple and selective analytical method becomes important for the determination of morachalchone A in ethanol extract 80% sample. The purpose of this study was to develop and validate a simple and selective High Performance Liquid Chromatography (HPLC) for determination of morachalchone A in ethanol extract 80% sample.This method was performed using a RP-18 Column 5μm (250 x 4.6 mm i.d) as stationary phase, isocratic mobile phase of acetonitrile : water (50:50 v/v) with flow rate 1.0 ml/minute, injection volume 20 μl and analytical wavelength at 368 nm. The results showed that method was selective to separate morachalcone A from other component with good resolution. Retention time morachalcone A was 21.520 minute. The data for calibration plots showed good linear relationship with r = 0.999 in the concentration range 1.93 - 7.71 ppm. The limit of detection and quantification were found 0.26 ppm and 0.86 ppm, respectively. The mean of % recovery addition standard method in 80%, 100% and 120% was found 102,72% ±2,47; 97,37% ±2,18 and 96,66% ±0,80. The relative standard deviation for repeatability and intermediate precision was 4.47% and 3.19% respectively. The marker content in ethanol extract of Artocarpus champeden SPRENG stembark was shown as mean ± SD (RSD) of 0.0151% ± 0.0002 (1.83%)